Asia bond monitor, June 2019. ([Manila] Asian Development Bank, 2019)
At the end of March, there were 15 trillion in local currency bonds outstanding in emerging East Asia, 2.9% more than at the end of 2018 and 14.0% more than at the end of March 2018. Bond issuance in the region amounted to 1.4 trillion in the first quarter, 10.0% higher than in the last quarter of 2018 on the back of stronger issuance of government debt.
Keywords: Finance; Financial institution; Electronic books